Innovative Activity and its Sources of Uncertainty: A Comprehensive Taxonomy - Ramírez Rodríguez, Liliana; Rivera González, Gibrán (Unidad Editorial UPTC, 2024)
The only certainty in innovation is uncertainty. The prevalence of heterogeneous unknowns, the novelty, non-standard, complex, multivariable, and interdependent character make innovation a reasoned process under uncertainty. When the adverse effects of this process are described, it is often done by referring to the terms risk and uncertainty interchangeably, given the diffuse boundary between the two. However, this confusion can lead to making poor quality decisions by assuming that they are familiar with important variables that arise from the innovation when in fact they are not. Given this theoretical and empirical disparity and ambiguity detected, this work develops an analysis of the concept of uncertainty, identifies its key characteristics and offers a taxonomy of the sources that originate it in the context of innovation. Through a mixed literature review analysis, an uncertainty proposition is presented that integrates perception, cognition processes, cognitive limitations, the information and/or knowledge gap, quality, and its accessibility, as well as inference and the construction of subjective models that give meaning to the situations experienced. In addition, the results provide the identification of five key characteristics and nine sources of uncertainty: 1) Political - Economic, 2) Sociocultural - Socioenvironmental, 3) Market, 4) Cooperation, collaboration, and co-innovation relations, 5) Technical - Technological, 6) Financial Capital, 7) Human intellectual capital, 8) Corporate governance - Operational interdependencies and 9) Commercial. JEL Codes: O30, O31 Received: 26/09/2023.  Accepted: 14/04/2024.  Published: 18/05/2024.